Pseudotypes: your flexible friends - King, Barnabas; Daly, Janet M. (Future Medicine, 2014)
Pseudotype viruses: applications and troubleshooting' (EuroSciCon 2013), a 1-day conference held at Cineworld: The O2 (London, UK) on 2 October 2013, focused on the technique of pseudotyping enveloped viruses (for a review of the technique, see [1]). The talks and posters covered the challenges and successes of pseudotyping viruses from a broad range of families (Retroviridae, Flaviviridae, Orthomyxoviridae, Bunyaviridae and Rhabdoviridae) for a variety of applications. The conference was chaired by Nigel Temperton, University of Kent (UK), who placed a strong emphasis on using this event to explore the technical challenges of pseudotyping viruses, especially during the poster and afternoon question and answer sessions.